Do the ten Mohist theses represent Mozi's thought? Reading the masters with a focus on mottos1. (13th June 2014) - Defoort, Carine
Abstract In order to introduce Mozi's thought, almost every contemporary textbook on Chinese philosophy refers to his ten novel theses or dogmas, which have been preserved as the titles of the Core chapters (8–37): to elevate the worthy, to conform upward, to care for all, to condemn military aggression, to moderate expenses as well as burials, to acknowledge the will of Heaven and the percipient ghosts, and to condemn music as well as fatalism. Through a close reading of the Mozi and other early sources written by or attributed to masters, this paper argues, first, that these ten core ideas may not have been promoted by the earliest spokesmen of Mohism but gradually emerged while various layers of the book Mozi were written, and, second, that these ten ideas were not consistently attributed to early Mohism by Zhou and Han masters: their association of Mo with these specific mottos is limited and inconsistent. A focus on the most well-known motto – "care for all" – shows that there was no awareness of its belonging exclusively to one thinker or school. The difference between the earliest and the contemporary characterizations of Mozi sheds new light not only on early Mohism, but also on our preconceptions when reading early sources.